Kontribusi Kekuatan Otot Lengan dan Panjang Lengan Terhadap Kemampuan Servis Atas Pada Ekstrakurikuler Bolavoli Putra SMP N 1 Grobogan - Bayu Aji Santoso; Agung Wahyudi; Adi S; Fery Darmanto (Indonesian Journal for Physical Education and Sport, 2024)
There is a decline in achievement and many students fail to perform the upper serve. This study aims to determine the contribution of arm muscle strength and arm length to the ability to serve over the men's extracurricular bolavoli SMP N 1 Grobogan. This research instrument is a measurement of arm muscle strength using a pull and push dynamometer, measurement of arm length using anthropometry, and a bolavoli top serve test using AAHPER. Data analysis used, namely descriptive analysis, prerequisite test, correlation test (product moment and multiple correlation), and determination coefficient test. The results of the research analysis showed that: There is a contribution of arm muscle strength to the ability to serve over the men's volleyball extracurricular of SMP Negeri 1 Grobogan of R Square = 0.543 or 54.3%, (2) There is a contribution of arm length to the ability to serve over the men's volleyball extracurricular of SMP Negeri 1 Grobogan of R Square value = 0.240 or 24%. (3) There is a contribution of both arm muscle strength and arm length to the ability to serve the men's extracurricular bolavoli at SMP Negeri 1 Grobogan of R Square = 0.578 or 57.8%.